Advancing the Science of Vaccine Safety During the Coronavirus Disease 2019 (COVID-19) Pandemic and Beyond: Launching an International Network of Special Immunization Services . (9th June 2022) - Top, Karina A; Chen, Robert T; Levy, Ofer; Ozonoff, Al; Carleton, Bruce; Crawford, Nigel W; Creech, C Buddy; Kochhar, Sonali; Poland, Gregory A; Gutu, Kimberley; Cutland, Clare L
Abstract: Within 2 years after the start of the coronavirus disease 2019 (COVID-19) pandemic, novel severe acute respiratory syndrome coronavirus 2 vaccines were developed, rigorously evaluated in large phase 3 trials, and administered to more than 5 billion individuals globally. However, adverse events of special interest (AESIs) have been described post-implementation, including myocarditis after receipt of messenger RNA (mRNA) vaccines and thrombosis with thrombocytopenia syndrome after receipt of adenoviral vector vaccines. AESIs are rare (<1 to 10/100 000 vaccinees) and less frequent than COVID-19 complications, though they have associated morbidity and mortality. The diversity of COVID-19 vaccine platforms (eg, mRNA, viral vector, protein) and rates of AESIs both between and within platforms (eg, higher rate of myocarditis after mRNA-1273 vs BNT162b2 vaccines) present an important opportunity to advance vaccine safety science. The International Network of Special Immunization Services has been formed with experts in vaccine safety, systems biology, and other relevant disciplines to study cases of AESIs and matched controls to uncover the pathogenesis of rare AESIs and inform vaccine development. Abstract : Seizing the opportunity coronavirus disease 2019 (COVID-19) vaccination programs present to advance vaccine safety science, a new international network aims to apply a systems biology "adversomics" approach to characterize the mechanisms that underlie rare adverse events following immunization with potential to improve vaccine safety